Capillary electrophoresis study of systemin peptides spreading in tomato plant. Issue 2 (11th October 2018) - Mucha, Piotr; Ruczynski, Jaroslaw; Dobkowski, Michal; Backtrog, Ewelina; Rekowski, Piotr
Abstract: Systemin (Sys) is an 18‐aa plant peptide hormone involved in the regulation of plant's defensive response. Sys is considered as a fast‐spreading systemic wound signal. We developed a simple and rapid CE method to monitor the spreading of Sys peptides through tomato plant. A 1, 2, 3‐triazole‐linked AZT‐systemin conjugate was designed as a model to study the possibility of translocating small cargo molecules 3'‐Azido‐2', 3'‐dideoxythymidine by systemin. The Sys peptides (Sys, N ‐propiolyl Sys, and AZT‐systemin conjugate) were injected into the stem and leaves of mature tomato plant. Its transportation throughout the plant tissue was traced by CE. The peptides were clearly visible in the crude tomato exudates and an optimum separation was achieved in 25 mM phosphate "buffer" at pH 2.5 and a voltage of 20 kV using uncoated fused silica capillary. CE analysis showed that Sys peptides are well separated from tomato plant exudates ingredients and are stable in tomato stem and leaf exudates for up to 24 h. CE study revealed that the Sys peptides are effectively spreading throughout tomato stem and leaves and the peptides could be directly detected in the crude plant matrixes. The translocation was strongly inhibited by sodium azide. The results showed that the established CE method can be used to characterize plant peptides spreading under plant physiological conditions.